The Antimicrobial Activity of Carissa carandas L., Ficus carica L., and Olea europaeae L. Leaves Extracts on Growth of some Pathogenic Microorganisms - Shafeeq, May H; Omar-Zahid, Lina A; Sidkey, Ban A J (Al-Nahrain Journal of Science, 2018)
Plant extracts were approved to heal many diseases, so three medicinal plants namely Carissa carandas L., Ficus carica L. and Olea europaeae L. were collected from different regions of Baghdad, in which their ethanolic crude extracts of leaves were assayed for antimicrobial activity against various pathogenic microorganisms such as: Gram-negative bacteria (Escherisha coli, Pseudomonas aeruginosa), Gram-positive bacteria (Staphylococcus aureus, Bacillus subtilis), yeast (Saccharomyces cerevisiae) and fungi (Penicillium species). Antimicrobial activity was conducted by the agar well diffusion method. The plant leaves extracts showed various levels of antimicrobial activity on different test microorganism, Gram negative bacteria, S. aureus and yeast were sensitive to the leaves extracts of the three plants, while B. subtilis and the fungus showed a moderate sensitivity against the leaves extracts of the three plants. The crude leaves extract of Ficus carica L. showed higher effect than the other two plants against pathogenic microorganisms.